2018
DOI: 10.1007/s11145-018-9876-z
|View full text |Cite
|
Sign up to set email alerts
|

Visual-motor integration and reading Chinese in children with/without dyslexia

Abstract: Visual-motor integration is an ability to coordinate the visual information and limb movement, which has direct relevance to Chinese handwriting ability. Interestingly handwriting practice can also improve Chinese reading. However, the relationship between visual-motor integration and reading ability in Chinese is unclear. The present study investigated the role of visual-motor integration skills in reading Chinese among children with and without developmental dyslexia. In the study Chinese children with devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 57 publications
0
12
0
1
Order By: Relevance
“…Classen et al (1998) also reported a decrease in activation coherence in the beta band in a visuomotor force-tracking task but not in visual-or motor-only tasks, suggesting that beta oscillations are related to visuomotor integration (Classen et al, 1998;Kilavik et al, 2013;Müller et al, 2003). Visuomotor skills are particularly important to Chinese reading (Meng et al, 2018;Tan et al, 2005b), and deficits in visuomotor integration have been observed in Chinese dyslexic children in previous behavioral studies (Cheng-Lai et al, 2013;McBride-Chang et al, 2011). Visuomotor integration was not directly assessed in the present study.…”
Section: Network Topology In the Beta Bandmentioning
confidence: 48%
“…Classen et al (1998) also reported a decrease in activation coherence in the beta band in a visuomotor force-tracking task but not in visual-or motor-only tasks, suggesting that beta oscillations are related to visuomotor integration (Classen et al, 1998;Kilavik et al, 2013;Müller et al, 2003). Visuomotor skills are particularly important to Chinese reading (Meng et al, 2018;Tan et al, 2005b), and deficits in visuomotor integration have been observed in Chinese dyslexic children in previous behavioral studies (Cheng-Lai et al, 2013;McBride-Chang et al, 2011). Visuomotor integration was not directly assessed in the present study.…”
Section: Network Topology In the Beta Bandmentioning
confidence: 48%
“…In Chinese characters, the parameters of the handwriting product are measured by the number of words written out of the grid, word size, and the numbers of the wrong stroke, additional stroke, missing stroke, concatenated stroke, and reverse stroke. According to Meng, Wydell [25], writing Chinese characters requires children to discriminate against the difference in the structures of characters through the visual-motor abilities to coordinate finger motion and basic visual input. This further explains why VMI and MEM were significantly related to the Chinese handwriting product.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that deep orthographic processing decodes characters by utilizing the spatial relation of strokes both visually, through the visual analysis decoding system, and sequentially, through the motor gesture decoding system. It has been shown that children's visual‐motor integration ability during writing effectively predicts their reading performance (Meng et al., 2018; Zemlock et al., 2018). Through visual‐motor integration, writing motor and visual orthographic information mutually contribute to deep orthographic processing.…”
Section: Discussionmentioning
confidence: 99%